MAINSTREAMING FIQH SIYASAH DALAM KEPEMIMPINAN BERDASARKAN PRINSIP PANCASILA - El Naqia Sari; Martunus Rahim (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2023)
Leadership is still an interesting issue in the life of the nation in Indonesia. It is a concept that covers various aspects of how leaders influence and interact with their followers in communicating common goals. When talking about the country, leadership must have a core principle of leadership. Including Indonesia, which has a state foundation called Pancasila. This study is important to see how fiqh siyasa views leadership based on the guidelines of “kemanusiaan yang adil dan beradab” in Pancasila. This research was conducted using a qualitative method with a philosophical approach by analyzing the meaning of one of the Pancasila precepts with Islamic religious principles normatively and philosophically. This principle finds that First, leadership that is “Berperikemanusiaan”  in Pancasila intends to uphold human dignity and protect human rights. Human Rights have long been recognized in Islam as explained in the Al-Quran (QS Shaad: 71-72); Second, the guidance of the Pancasila Law is reflected in the prosecution of Indonesian citizens through law regardless of their class and rank. In addition, many verses in the Al-Quran explain justice, one of which is Q.S Shaad: 26; Third, “beradab” of leadership in Pancasila means a leader follows good standards of behavior. Islam teaches that a believer is a person with commendable morals, which includes politeness.